Vibrational spectra of polaprezinc, a polymeric Zn(II) complex of carnosine - Wagner, Claudia Cecilia (2008)
Polaprezinc, the Zn(II) complex of the dipeptide carnosine (b-alanyl histidine) presents an interesting biological and pharmacological activity, specially as an anti-ulcer agent. The infrared and Raman spectra of this compound were recorded and briefly discussed. Some comparisons were made with related complexes and with free carnosine. The results confirm the coordination environment of the Zn(II) cation, constituted by the terminal amino N-atom, the deprotonated amide N-atom and one carboxylate oxygen of one dipeptide molecule and the N-atom of the imidazole moiety of a second carnosine molecule.